COST DEVELOPMENT ISSUES IN OIL& GAS-PRODUCING COMPANIES - Nikolay N. Vorobiev; Svetlana V. Pushkareva (Вестник Северо-Кавказского федерального университета)
The item focuses on various issues of cost development in oil & gas-producing companies. The author provides an analytical explanation and classification of costs, together with a view on various calculation methods for tracking and distribution of costs in supporting departments depending on the area of the activities performed.